(untitled) (Zaporizhzhia Historical Review, 2021)
The article is dedicated to the problem of endogamy in the Mennonite ethnic-religious group during 1789 – 1917. It has been considered that deterioration of mental and physical health of Mennonites became backside of saving of religious and ethnic traditions in communities by the way of normative endogamy.